Influence of Preclinical Training on Root Canal Treatment Technical Quality and Confidence Level of Undergraduate Dental Students - Reem M. Barakat; Manal Matoug-Elwerfelli; Rahaf A. Almohareb; Hanan A. Balto (Hindawi Limited, 2021)
Objectives. The aim of this study was to investigate the influence of exposure to additional preclinical endodontic training on undergraduate students' technical quality of root canal treatment and overall confidence levels in endodontics. Methods. Technical quality of root canal treatment performed clinically by fifth-year undergraduate students was evaluated and divided into two groups: Group 1, teeth treated by students who had attended both a preclinical endodontic block course and an elective preclinical course. Group 2: teeth treated by students who had not attended the elective preclinical course. All students were also invited to participate in a survey to rate their undergraduate endodontic training and confidence levels performing endodontic treatment. Statistical analysis of data was performed using Person chi-square test, Fisher Freeman Halton exact test, and t-test. A p-value <0.05 was considered statistically significant. Results. There was no significant difference between the two groups in overall obturation quality (p=0.619). However, more teeth treated by attendees were of adequate obturation length (p=0.015) and lacked procedural errors (p=0.004). Significantly more elective course attendees rated their undergraduate endodontic training as adequate (p=0.002), but there was no significant difference in the level of confidence between the attendees and the non-attendees. Conclusion. Within the limitations of this study, additional preclinical training showed minimal effect on overall quality of root canal treatment performed clinically by undergraduate students and did not enhance their confidence levels; however, it was associated with more satisfaction with their undergraduate endodontic education.